My nest isn't empty, it just has more closet space [compact disc, unabridged] : the amazing adventures of an ordinary woman - Scottoline, Lisa (Macmillan Audio, 2010)
Best selling author Lisa Scottoline presents her second memoir. Inspired by her weekly column in the Philadelphia Inquirer, Scottoline offers an updated account of her personal life. From her relationships with her ex-husbands to her adult daughter moving away from home, Scottoline's wit and humor will delight fans and casual listeners alike.